Hubungan Tingkat Kejadian Diabetes Melitus Terhadap Kondisi Hipertensi Di Indonesia - Hita, I Putu Agus Dharma; Pranata, Doni (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2021)
Diabetes mellitus and hypertension are one of the many diseases that are very dangerous to the health of the body, even a disease that has a high mortality rate. This study aims to determine the relationship between diabetes mellitus incidence rate and hypertension condition in Indonesia. This type of research is a type of correlational research using simple regression techniques with the help of the SPSS 22 for Windows application. The data used in this study are data from the National Basic Health Research Report 2018. The sample in this study were all citizens of the Republic of Indonesia in 2018 who experienced diabetes mellitus and hypertension conditions. The results of this study are that there is a relationship between the incidence rate of diabetes mellitus and the condition of hypertension in Indonesia in 2018 with a relationship level of 56.4%.